Bilateral Metachronous Paget's Disease of the Accessory Breasts in a Male - Lee, Young Joo; Shin, Junyoung; Jung, Jin-Min; Kim, Eun Key; Jung, Jinhong; Jeong, Jae Ho; Gong, Gyungyub; Ko, BeomSeok (Journal of breast cancer, 2020)
Bilateral axillary Paget's disease in men is a rare occurrence with limited reports on its diagnosis, treatment, and prognosis. Here, we report the case of a 55-year-old Korean male, who presented with a palpable mass and eczematous skin lesion on the left axilla. An incisional biopsy and histopathologic examination indicated invasive ductal carcinoma with Paget's disease arising in the accessory breast. Magnetic resonance imaging and positron emission tomography revealed no malignancy in the normal breast and other organs. The patient was subjected to a wide excision, wherein the left axillary lymph node was dissected, followed by the administration of adjuvant chemotherapy and radiation therapy. After 17 months of disease-free survival, the patient was diagnosed with Paget's disease of the contralateral accessory breast. He underwent wide excision surgery along with radiation therapy. To the best of our knowledge, this is the first report of bilateral extramammary Paget's disease in a male.